Właściwość wojewody w zakresie zapewnienia bezpieczeństwa i porządku publicznego oraz zapobiegania zagrożeniu życia i zdrowia - Karpiuk, Mirosław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
One of the fields in which public administration performs its task is security. The voivodeship governor is a part of public administration as they are equipped with security measures related to public order and the protection of life and health. They undertake actions to prevent, control and deal with extraordinary situations and their consequences. Due to the need to adapt protective measures to the threat and the need to harmonize them, in cases provided by the law, the governor may also undertake managing and coordinating activities in the area of the region. It is a body that has broad competencies to shape the field safety system at the voivodeship level.